Examining the Participation of Female Peacekeepers in the United Nations Peacekeeping Operations: The Contributions of Islamic Countries - Ridha Nahdhiyah Alma Amaliyah; Hadidah Sallimi; Surwandono Surwandono (The Republic of Indonesia Defense University, 2023)
The world of International Relations will never be separated from its history. Countries in the Middle East, especially Muslim-majority countries, still have a lot of conflicts going on. However, the contribution of Islam to the world of peace never stops. In the contemporary world, for example, this contribution is realized through the participation of Islamic countries in United Nations Peacekeeping Operations (UN PKO). This study aims to analyze the contributions of female peacekeepers of Islamic countries. This research uses the concept of peacekeeping and analyzes secondary data with the quality method and literature review approach as the data collection technique. The result of this research shows that eight of 12 peace missions involved Muslim-majority countries such as Bangladesh, Pakistan, Egypt, and Indonesia, which sent the most female peacekeepers. This study found that the Muslim-majority countries have successfully implemented the UN PKO program, especially for the increasing number of female peacekeepers agenda. It also found that the female peacekeeper has a substantive and public function in the operations, such as their contribution to the operation in logistical, informational branches, and medical aid aspects. However, the UN PKO still emphasizes masculinity. This study shows that domestic issues including inadequate military personnel and social stigmatization of women's peacekeeping engagement greatly reduce women's representation in UN peacekeeping operations. This inherently impacts the Women, Peace, and Security agenda.